PENGARUH APLIKASI KOMPOS Crotalaria juncea L. TERHADAP KETERSEDIAAN DAN SERAPAN CA, Mg, S OLEH JAGUNG MANIS (Zea mays saccharata Sturt) DI ENTISOL WAJAK, MALANG - Retno Suntari; Muhammad Abdi Guna Wiyahya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Entisol is a type of soil at the initial development stage and has a texture dominated by sand fraction. This causes a decrease in soil quality and can reduce crop production. This compost of leguminase plants can play a role in improving soil chemical properties. The purpose of this research was to determine the effect of Crotalaria juncea L. compost application on the availability of secondary macro nutrients Ca, Mg, and S, and uptake of Ca, Mg, and S by sweet corn plant in Entisol, Wajak. Treatments tested were C0 (Urea 100%), C1 (Compost Crotalaria juncea L. 100% + Urea 75%), C2 (Compost Crotalaria juncea L. 100% + Urea 75%), C3 (Compost Crotalaria juncea L. 100%), C4 (Compost Crotalaria juncea L. 200%). The five treatments were arranged in a completely randomized design with three replications. The results showed that the application of Crotalaria juncea L. compost (20 t ha-1) significantly increased the availability of Ca, Mg and S on 12 weeks by 41.6%, 96.71% and 133.78%, respectively. The application of Crotalaria juncea L. compost (20 t ha-1) did not significantly increase uptake of Ca, Mg and S.